Coalescence of oil drops and films on micropillared substrates enabled by enhanced water drainage through pillar gaps. Issue 24 (24th May 2021) - Park, Chan Jin; Ha, Jonghyun; Lee, Jae Hong; Kim, Ho-Young
Abstract : We find that an oil drop colliding with a micropillar array wetted by an oil film immediately coalesces with the film instead of bouncing off, owing to enhanced water drainage through the pillar gaps. Abstract : Collecting or removing oil drops dispersed in water is essential in a range of industrial processes including oil recovery and oil spill cleanup. However, it is by no means easy to induce merging of oil drops with another body of oil due to slow drainage of the intervening water film. Here, we report immediate coalescence of oil drops with oil films that lie on micropillar arrays as immersed in various aqueous solutions. In addition to experimental demonstrations, we theoretically construct a regime map to predict whether the drop will bounce off or coalesce with the oil film, which is determined by the oil film thickness, geometry of the pillar array and liquid properties. Good agreement between theory and experiment indicates that micropillar arrays provide additional drainage paths of the intervening film, which helps drop–film coalescence. Our results suggest potential implications of utilizing oil-laden microporous structures to achieve efficient demulsification of oil drops in contaminated water.